The Health Returns of University Eligibility - Gawain Heckley; Martin Nordin; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2020)
This paper exploits an arbitrary university eligibility rule in Sweden combined with regression discontinuity to estimate the impact of university education on health derived demand for medical care. We find a clear jump in university attendance due to university eligibility of between 10 and 14 percentage points. For females this implies a 30-40% drop in self-harm. For males it coincides with reduced use of prescribed pain killers, implying reduced risky behaviour. Males also observe a 30% increase in mental disorders, almost exclusively related to alcohol. The spillovers of university education on to health for the marginal student are therefore significant.
Keywords: I10; I23; I26; 330; Health returns to education; demand for medical care; Regression Discontinuity Design